(untitled) (Baghdad Science Journal, 2016)
In this paper to isolate and study the properties of the cyclooxygenase-2 (EC: 1.14.99.1) enzyme in the blood of a patient suffering from rheumatoid arthritis and study the effect of natural products of the Soapwort on the activity of purified enzyme. The study involves taking 30 ml of blood from an adult woman 40 years old, who suffers from rheumatoid arthritis disease for 13 years. Serum is separated and subjected to a series of purification processes including: precipitation by ammonium sulfate, filtration by centrifugation radiator, dialysis in presence of ammonium bicarbonate, separation using the technology of ion exchange, lipholization and then estimating approximate molecular weight of the enzyme using gel filtration technique and sodium dodecyl sulfate (SDS)-page polyacrylamide gel electrophoresis. The study also includes isolating the natural products of Soapwort plant and study the effect of isolated natural products on the activity of the purified enzyme. The result of the study indicates that cycloxygenase-2 has an approximate molecular weight of 71.5 kDa and that the extracted oil of the Soapwort has a negative impact on the activity of the enzyme (r= -0.824; P=0.006), while flavonoids and Saponin have no such impact (r= -0.565; P=0.113; r= -0.634; P=0.067 respectively).